PJMHS 2022
DOI: 10.53350/pjmhs20221611872
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Iron Deficiency Anemia in School Going Children at District Bannu Khyber Pakhtunkhwa, Pakistan

Abstract: Purpose: The purpose of the current research was to determine how common iron deficiency anaemia was among school-age children. Methodology: A total 200 blood sample in EDTA tube from school going children (6-12 year old) was collected at district Bannu KPK and then transported to Pathology Lab for Complete blood count using hematology analyzer and also transported for microscopy to evaluate the morphology of Red blood cells. Result: Total 200 blood samples were subject to Pathology Lab. Male was 110 (55%) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…Intestinal parasitic infection, due to poor hygienic conditions interferes with iron absorption, thus expanding the prevalence of iron deficiency anemia in the developing world [41][42][43]. In the present study, the observed association between parasitic infestations and anemia has been reported in several other studies worldwide [44][45][46]. The prevalence of anemia in the current study was higher among underweight children when compared to children with normal BMI, overweight and obese children.…”
Section: Discussionsupporting
confidence: 77%
“…Intestinal parasitic infection, due to poor hygienic conditions interferes with iron absorption, thus expanding the prevalence of iron deficiency anemia in the developing world [41][42][43]. In the present study, the observed association between parasitic infestations and anemia has been reported in several other studies worldwide [44][45][46]. The prevalence of anemia in the current study was higher among underweight children when compared to children with normal BMI, overweight and obese children.…”
Section: Discussionsupporting
confidence: 77%
“…In addition, in another study conducted, it is stated that individuals may experience difficulty in leaving the social media environment by developing addiction as a result of continuous use of social media as a means of entertainment (Larose, 2011). In addition, it has been supported by the results of the relevant research that social media causes some problems in school and work life by negatively affecting the time management skills of individuals (Andreassen, 2015;Chou & Hsiao, 2000;Khan et al, 2017). In line with these studies, it can be said that the unconscious use of social media can cause some problems in both personal and academic and social life.…”
Section: Discussionmentioning
confidence: 94%
“…Some of the local studies in school-going children also showed a high prevalence of anemia. A study conducted by Sayab et al in district Bannu of Khyber Pakhtunkhwa showed that among 200 school-going children, mild anemia was noted in (41.66%), moderate anemia in (37.5%) and severe anemia was detected in 20.83% of school going children 25 . Almost similar results were noted in the present study.…”
Section: Discussionmentioning
confidence: 98%